Question type and its effect on children ' s maintenance and accuracy during courtroom testimony. Issue 2 (9th May 2016) - Saykaly, Christine; Crossman, Angela; Morris, Mary; Talwar, Victoria
Abstract : Purpose: – The purpose of this paper is to investigate the influence of question type (open-ended, prompted, reverse order and chronological order recall) on children's ability to maintain a truth or a lie in a two-part mock-courtroom study. Design/methodology/approach: – In total, 96 children ( M age =131.00 months) between 9 and 12 years of age were asked to testify about an interaction with a research assistant the week prior. They were assigned to one of four conditions (true/false×assertion/denial). Findings: – Results indicate that question type has an influence on children's ability to maintain their condition. Results also indicate that regardless of question type, children have difficulty recalling information sequentially. Practical implications: – Implications of the current research support the use of various question types, including increasing the cognitive load demands, when interviewing children. Originality/value: – To date, this is the first study to investigate the use of reverse order questioning in a courtroom study with children.